Faktor-Faktor yang Berhubungan dengan Kecendrungan Turnover Perawat di Rumah Sakit Islam “Ibnu Sina” Yarsi Sumbar Bukittinggi - Bambang Aryanto; Reni Prima Gusty; Yulastri Arif (NERS Jurnal Keperawatan)
High turnover is a problem in the management of human resources at hospitals. The nurse turnover rate at Islamic Hospital "Ibn Sina" Yarsi Bukittinggi, West Sumatra, has tended to rise each year, with data from 2009 and 2010 showing rates of 21.3% and 24.3%, respectively. The purpose of this research is to identify factors associated with nurse turnover trends at Islamic Hospital "Ibn Sina" Yarsi Bukittinggi, West Sumatra. This research uses a descriptive analytic cross-sectional study approach. The sample consisted of 75 people, and data was collected using questionnaires. Data analysis was conducted using the Chi-Square test. The results showed that 54.7% of nurses had a tendency to leave the hospital. There was a relationship between external factors, namely the availability of jobs in other institutions, and the tendency to leave (p-value 0.039). However, no relationship was found between internal organizational factors (such as the size of the organization, leadership, compensation, job satisfaction, career development, job weights, centralization) and individual employee factors with the tendency to leave. To reduce nurse turnover, it is important for hospital administrators to review programs aimed at addressing the issue. Such programs should focus on improvements in nursing leadership, career development, and efforts to enhance job satisfaction for nurses.